Pediatric Obesity—A Potential Risk Factor for Systemic Inflammatory Syndrome Associated to COVID-19, a Case Report - Mărginean, Cristina Oana; Meliţ, Lorena Elena; Săsăran, Maria Oana (Frontiers in Pediatrics, 2021)
The well-documented systemic inflammation associated to pediatric obesity might act as an augmenting factor for other inflammatory conditions, such as pediatric inflammatory multisystem syndrome (PIMS) associated to COVID-19. We report the case of 9-year-old boy admitted in our clinic for fever, anorexia, and fatigability. The clinical exam revealed influenced general status, palpebral edema, non-exudative conjunctivitis, and abdominal tenderness. The patient weighed 45 kg. The laboratory tests at the time of admission pointed out anemia, lymphopenia; elevated inflammatory biomarkers, NT-proBNP, D-dimers and troponin; high liver enzymes and lactate dehydrogenase levels, as well as hypoalbuminemia. The patient tested positive for both RT-PCR and serology for SARS-CoV-2 infection. We initiated intravenous immunoglobulin and methylprednisolone, associated with empirical antibiotic, anticoagulation therapy and symptomatic treatment. The patient was discharged on the 7th day of admission with the recommendation to continue enoxaparin and methylprednisolone at home tapering the dose for the next week. The subclinical inflammatory status associated to obesity might serve as an unfortunate trigger factor for the development of COVID-19 severe forms in children. Therefore, clinicians should be aware that children with obesity and COVID-19 represent a peculiar group that should be closely monitored and thoroughly assessed in order to preempt life-threatening complications, such as PIMS.